The effects of the Corona pandemic "Covid 19" and its relationship to the level of academic compatibility with university life among students of the University of Zakho - Abuzaid, Aras (Humanities Journal of University of Zakho, 2021)
The aim of the research is to know the effects of the Corona pandemic "Covid 19" and its relationship to the level of academic compatibility with university life among students of the University of Zakho, and to determine the statistically significant differences between the average of the sample scores on the scale of the effects of the Corona pandemic "Covid 19" and the measure of academic compatibility with university life according to the variables of sex and specialization. The researcher followed the descriptive and analytical approach, using the Corona Pandemic Impact Scale prepared by the researcher himself, and the University Life Compatibility Scale (ATCS) by Robert Baker and Bohdon Siryk, which was Arabized and prepared by Ali Abdul Salam Ali. The researcher applied the two measures on a sample of (230) students from Zakho University. The researcher reached several results, the most important of which are: -There is a strong negative and Reversible correlation between the effects of the Corona pandemic and the academic compatibility with university life among university students in the total degree and according to each field of research. -There are many strong negative effects of the Corona pandemic on the educational and psychological side of university students. - There is no statistically significant difference between the mean scores of Zakho University students on the scale of the effects of the Corona pandemic "Covid 19" and the scale of academic compatibility according to the variable of sex. - There is a statistically significant difference between the mean scores of Zakho University students on the scale of the effects of the Corona pandemic "Covid 19" and on the scale of academic compatibility according to the variable of specialization by the total degree.